2018
DOI: 10.1111/bjep.12215
|View full text |Cite
|
Sign up to set email alerts
|

Agency and responsibility in adolescent students: A challenge for the societies of tomorrow

Abstract: Structural equation modelling indicated that basic needs fulfilment positively predicts agency, responsibility, academic achievement, and career decision-making self-efficacy. Interpersonal justice positively predicts responsibility. The indirect effect from basic psychological needs on career decision-making self-efficacy through the mediating effects of student agentic engagement and student responsibility was significant. The indirect effect from interpersonal justice on career decision-making self-efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 72 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…The 25‐item Career Decision Self‐Efficacy Scale‐Short Form (CDSES‐SF) was designed to explore how individuals feel confident in their ability to successfully perform tasks in their career decision process (Betz et al, 1994; Taylor & Betz, 1983). This measurement scale has been identified and well fitted to a latent unidimensional structure and extensively applied in the current literature (Mameli, Molinari, & Passini, 2019; Miguel, Silva, & Prieto, 2013); therefore, this scale was adopted in this study. CDSES‐SF includes five career choice competencies: (a) accurate self‐appraisal, (b) gathering occupational information, (c) goal selection, (d) planning for the future, and (e) problem‐solving.…”
Section: Methodsmentioning
confidence: 99%
“…The 25‐item Career Decision Self‐Efficacy Scale‐Short Form (CDSES‐SF) was designed to explore how individuals feel confident in their ability to successfully perform tasks in their career decision process (Betz et al, 1994; Taylor & Betz, 1983). This measurement scale has been identified and well fitted to a latent unidimensional structure and extensively applied in the current literature (Mameli, Molinari, & Passini, 2019; Miguel, Silva, & Prieto, 2013); therefore, this scale was adopted in this study. CDSES‐SF includes five career choice competencies: (a) accurate self‐appraisal, (b) gathering occupational information, (c) goal selection, (d) planning for the future, and (e) problem‐solving.…”
Section: Methodsmentioning
confidence: 99%
“…Agentic engagement at the classroom level refers to the observable actions students take to express themselves in the learning process in terms of the extent to which students pose questions, express their preferences, opinions, or needs, communicate their interest, provide input and suggest alternatives, and request assistance (e.g., modeling), feedback, and concrete examples for abstract concepts (Reeve, 2013). This proactive engagement also arises from students' motivational states (e.g., psychological need satisfaction; Reeve & Tseng, 2011) and teachers' instructional supports (e.g., autonomy support, Matos et al, 2018) and positively predicts academic achievement (Reeve, 2013;Reeve et al, 2020) and career decision-making self-efficacy (Mameli et al, 2019). More importantly, agentic engagement links students' actions with teacher instructional behavior (Reeve et al, 2020) showing the "evocative impact" (p. 180) of students on teacher instruction (Nurmi, 2012).…”
Section: Agentic and Behavioral Engagementmentioning
confidence: 99%
“…Through metacognition (planning, goal-setting, self-monitoring, social processing, and help-seeking), students will build their capacity to monitor and become more responsible for their own learning (p 585). To help teachers and administrators to create programs in schools that will better develop students who can become responsible global citizens, Mameli et al (2019) confirmed the importance of providing experiences that help students to be "actors and protagonists of their own learning environment" (p 50). These experiences foster student agency, taking self-directed actions to regulate and monitor their own learning.…”
Section: A Revised Framework For International Mindednessmentioning
confidence: 99%